Oncological challenges in GFAP-positive anaplastic meningioma: a case report and literature review - Minh Huu Nhat Le; Nghia Minh Tran; Thinh Linh Ho; Ky Vo Pham; Quynh-Nhu Le Vo; Duy T. K. Huynh; Huynh Phuong Thao Do; Phat Tuan Nguyen; Michael J. Diaz; Nhi Huu Hanh Le; Han Hong Huynh; Dang Nguyen; et al. (Egyptian Pediatric Association Gazette)
Abstract Background Meningiomas are typically found in adults, with an average diagnosis age of 66. However, they can occur in children, presenting unique clinical and immunohistochemical characteristics. This report explores a rare pediatric case of anaplastic meningioma, highlighting the diagnostic and treatment challenges involved. Clinical finding, lab result, image result, histopathology result This patient’s clinical presentation and imaging studies suggested an intracranial tumor. Histopathological and immunohistochemical analyses confirmed a diagnosis of anaplastic meningioma. Notably, the tumor exhibited rare GFAP positivity, atypical for meningiomas, and a high Ki-67 index, indicating a significant risk of recurrence. Treatment The tumor was successfully removed surgically, and the patient recovered without complications. No additional therapy was planned. Conclusion Surgery is the primary treatment for symptomatic meningiomas, with generally low mortality rates in pediatric cases. This case emphasizes the diagnostic complexity of pediatric meningiomas with atypical features like GFAP positivity. Complete surgical removal of the tumor was performed, in accordance with guidelines. Detailed immunohistochemical analysis is crucial, and further research on similar cases is needed to improve our understanding and treatment strategies.